De novo variants in neurodevelopmental disorders—experiences from a tertiary care center. Issue 1 (1st March 2021) - Brunet, Theresa; Jech, Robert; Brugger, Melanie; Kovacs, Reka; Alhaddad, Bader; Leszinski, Gloria; Riedhammer, Korbinian M.; Westphal, Dominik S.; Mahle, Isabella; Mayerhanser, Katharina; Skorvanek, Matej; Weber, Sandrina; et al.
Abstract: Up to 40% of neurodevelopmental disorders (NDDs) such as intellectual disability, developmental delay, autism spectrum disorder, and developmental motor abnormalities have a documented underlying monogenic defect, primarily due to de novo variants. Still, the overall burden of de novo variants as well as novel disease genes in NDDs await discovery. We performed parent‐offspring trio exome sequencing in 231 individuals with NDDs. Phenotypes were compiled using human phenotype ontology terms. The overall diagnostic yield was 49.8% (n = 115/231) with de novo variants contributing to more than 80% (n = 93/115) of all solved cases. De novo variants affected 72 different—mostly constrained—genes. In addition, we identified putative pathogenic variants in 16 genes not linked to NDDs to date. Reanalysis performed in 80 initially unsolved cases revealed a definitive diagnosis in two additional cases. Our study consolidates the contribution and genetic heterogeneity of de novo variants in NDDs highlighting trio exome sequencing as effective diagnostic tool for NDDs. Besides, we illustrate the potential of a trio‐approach for candidate gene discovery and the power of systematic reanalysis of unsolved cases. Abstract :